Foreword - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
Dear Colleagues, dear Friends, dear Students. This particular year, which has seen us forced into a long lockdown and into changing our working habits, marks the 4th of Ash Sharq. This unconventional journal which prioritises rapid publication, has found its audience and has gained the loyalty of its authors. I thank you very much, readers and authors, you have made the continuation of the journal possible. We have decided this year to streamline our mode of publication. We shall now publish two online issues and one combined print issue per year. When the first issue is ready we shall post it online for digital subscribers; when the second issue is ready we shall post it online in the same way, and also create a combined print edition of the two issues for circulation to print subscribers. Each issue will be ‘final’. We shall not publish ‘work in progress’ papers for updating later. One exception is this fourth number, which includes both the first and second issues for 2020.